Oxygen Saturation as a Predictor of Adverse Maternal Outcomes in Women with Preeclampsia - Rani, Sweta; Mistri, Pallab Kumar (Birat Journal of Health Sciences, 2019)
Introduction: In preeclampsia, hypoxemia may result from a number of mechanisms. Preeclampsia remains a complex and poorly understood disease. Currently, there are no reliable predictors of preeclampsia for early diagnosis to avoid adverse maternal or perinatal outcomes. Objective: The objective was to evaluate the efficacy of oxygen saturation (SpO2) as a predictor of adverse maternal outcome in women with preeclampsia. Methodology: We conducted the cross-sectional study on 182 preeclamptic women selected by random sampling technique. They were divided into two groups on the basis of oxygen saturation: 29 preeclamptic women (Group L) having oxygen saturation 95% or below and 153 women (Group H) having oxygen saturation 96% or above. The groups were statistically compared with respect to age, gestational age, proteinuria, severity of hypertension and developing different adverse effect of preeclampsia. Women with any medical disorders were excluded. Results: After statistical analysis, it was seen that the women having Spo2 ≤ 95% (L-Group) had experienced more adverse 2 outcomes. They were more hypertensive and more proteinuric, had higher liver enzyme levels, lower platelet counts, and were more likely to have experienced cardio-respiratory symptoms. Women with adverse outcomes were also more likely to have had therapeutic interventions, including corticosteroids, antihypertensives, and magnesium sulphate. Conclusion: Women having SpO2 ≤ 95% (L-Group) had more adverse 2 outcomes in comparison to SpO2 ≥96%(H-Group).